Formalism and Power of Language: Unravelling the Narratology of Final Fantasy XVI - Wibowo, Agung Prasetyo; Suyudi, Ichwan; Purnomo, SF Luthfie Arguby; Firmawan, Hendro; Khatib, Ahmad Juma (Langkawi: Journal of The Association for Arabic and English, 2024)
Using the framework of formalist analysis, this study examines how language serves as a source of power in shaping the narrative depth, character development, and thematic exploration of Final Fantasy XVI. This research involves analyzing various types of language, from dialogue and narration to symbolism, metaphor, and simile. The research methodology employed is qualitative analysis, allowing for an in-depth examination of the linguistic complexities present in the game through textual analysis and content analysis. By thematically dissecting language and applying techniques from formalist linguistics, such as Deixis Analysis, the study aims to determine how game creators purposefully use linguistic techniques to construct emotional connotations and expressive effects. Additionally, it explores how witty dialogues between characters contribute to the development of story-related themes. This study reveals how the linguistic fabric of Final Fantasy XVI functions as an effective tool in crafting an engaging and powerful story. It draws players deeper into the game's world and evokes their sympathies for the various forces at play. Furthermore, the research highlights the intentional use of linguistic devices to enhance narrative immersion and emotional impact, showcasing the intricate interplay between language and storytelling in video games. Through this analysis, the study underscores the significance of linguistic elements in video game narratives, providing insights into how language can be manipulated to create compelling and immersive experiences for players.